HUBUNGAN STRES DAN KUALITAS TIDUR: TINJAUAN LITERATUR - Septian, Niko (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Stress is the body's reaction to situations that seem dangerous and difficult, causing the body to produce the hormone adrenaline to defend itself. Determined by the researchers is a major factor in sleep difficulties in the short term. The purpose of this literature review is to analyze the relationship between stress and sleep quality. Library data collection which was carried out from 12 articles found the 5 most relevant articles in this study. The results of the analysis show that the level of severe and moderate stress can lead to poor sleep quality and can cause serious complications such as insomnia and hypertension. The results of the literature review show that stress is the main cause of sleep quality based on the levels. Therefore, researchers can conclude that there is a significant relationship between the effect of stress and sleep quality.